Modeling Fatty Acid Transfer from Artery to Cardiomyocyte - Arts, Theo; Reneman, Robert S.; Bassingthwaighte, James B.; van der Vusse, Ger J. (PLOS Computational Biology, 2015)
Author Summary The energy required for pump work of the heart is generated primarily by oxidation of long-chain fatty acids (Fa), transferred to the heart by plasma albumin. In coronary capillaries, Fa detach from albumin, cross endothelial cells, pericapillary interstitium and cardiomyocyte membrane prior to oxidation. The exact mechanism underlying the transfer process, however, is unknown. We designed a computer model of this Fa transfer using parameter values in the physiological range. We postulate that known physical principles of diffusion, Fa-protein complex binding, and Fa solubility in water and lipid membranes can describe intra-cardiac transfer. Model simulations were compared with multiple indicator dilution experiments, administrating a bolus of labeled Fa and albumin into the coronary artery. The resulting dilution time courses of label concentrations in the coronary veins compared favorably with the model simulations. We conclude that the model appears to be realistic, providing a useful tool to study in detail the mechanisms of intra-cardiac Fa transfer.